AN OVERVIEW OF THE LEGAL POWER OF DEAF DISABILITY TESTIMONY AS EVIDENCE IN RAPE CRIMINAL CASES - Pitoyo; Herwin Sulistyowati; Erna Wati (Bajang Institute, 2023)
Law cannot be equated with a machine tool, but the law is loaded with the role played by humans themselves (law enforcement and society). In the success of law enforcement depends on the individual man himself, because it is humans who carry out the law order itself. Since the presence of humans on earth, humans have an important role in the implementation of law enforcement itself, humans who create their own laws then humans must also follow the rules of law. This research method uses literature studies. The type of research carried out is normative legal research, which is research conducted by examining secondary data. Normative legal research in the form of legal norms of laws and regulations that are studied vertically and horizontally.